DIFFERENCES IN BODY WEIGHT AND INFECTION ON INFANTS 0-6 MONTHS FEEDED FORMULA AND EXCLUSIVE BREAST MILK - wati, Roslina; anti, Novi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Adequate breast milk not only supports healthy growth, but also cognitive development and long-term health of the baby. It is recommended that babies should be exclusively breastfed for the first 6 months to get optimal growth, development and health. Infants who were exclusively breastfed had normal weight overall, and none were overweight (obese) or even malnourished. So that breast milk is the main, best and first natural food for babies given without additional food at least until the age of 4 months and if possible until the age of 6 months. Breast milk is proven to protect children against various infectious diseases such as diarrhea, ARI and others. The purpose of this study was to analyze differences in body weight and incidence of infection in infants 0-6 months who were given formula milk and exclusive breastfeeding in the Nibong Health Center Work Area, North Aceh Regency in 2021. Type of observational analytic research with cross-sectional study design. The research stages are: 1) Preliminary Survey 2) Data collection using questionnaires, 3) Data Processing and Analysis. The trial subjects of this study were parents who had babies aged 0-6 months as many as 126 people, 63 babies 0-6 months who were given exclusive breastfeeding and 63 babies 0-6 months who were given formula milk. Data were analyzed using bivariate analysis using independent T-test. The results of the study were that there was a difference in the weight of infants 0-6 months fed formula and breast milk (p=0.047), there was a difference in the incidence of diarrhea in infants 0-6 months fed formula and breast milk (p=0.00) and there was a difference in the incidence ARI for infants 0-6 months who were given formula milk and breast milk (p=0.04). Mandatory output in the form of an accredited national journal. The technology readiness level of this research is 2.